Development of a Dental Practice Medical Record Using The Scrum Methodology - Christshanty, Debora; Pande, K. Agus Andhika Putra; ER, Ngurah Indra; Purnama, Fajar (Journal of Electrical, Electronics and Informatics; Vol 8 No 1 (2024): JEEI (June 2024), 2025)
Dental practices in Jimbaran area currently record medical records manually. This leads to potential data inaccuracies, longer wait times for patients, and difficulties in tracking patients' medical histories. An information system for dental practice medical records was designed to address these issues. The development method employed in this study is the Scrum methodology. The advantage of the Scrum method is that it ensures the final product meets user needs by actively involving users in the information system development process. The findings of this research have been developed into a Dental Practice Medical Records Information System to assist dental practices in recording their medical records.